Teaching and applying telepractice for hearing and balance disorders in Africa in the COVID-19 era and beyond - Katijah Khoza-Shangase (Discover Global Society)
Abstract Background The COVID-19 pandemic necessitated widespread adoption of telepractice to ensure the continuity of healthcare services, including those for individuals with hearing and balance disorders. In Africa, where access to specialized healthcare services is often limited, telepractice emerged as a potential solution. However, the implementation of telepractice in African contexts faces unique challenges. Aim This narrative review aims to synthesize the available literature on the teaching and application of telepractice for hearing and balance disorders in the African context following the COVID-19 pandemic. The review explores barriers and facilitators to telepractice implementation and identifies gaps in knowledge to inform future research, policy, and clinical practice. Methods A narrative review approach was adopted to provide a broad and interpretive synthesis of the literature. Thirteen relevant publications were identified, focusing on the period between January 2020 to current. Publications were selected based on their contribution to the understanding of telepractice in managing hearing and balance disorders, with key themes analysed to explore recurring patterns and insights. Saturation was reached when no new themes emerged during the review process. Results Six key themes emerged from the analysis: (1) accessibility and reach of telepractice; (2) technological infrastructure and digital literacy; (3) training and capacity building; (4) barriers in resource-limited settings; (5) facilitators for adoption of telepractice; and (6) sustainability and future of telepractice in Africa. These themes reveal that while telepractice has significantly improved accessibility to audiology and balance services, particularly in remote areas, its implementation is hindered by poor internet connectivity, limited digital literacy, and inadequate infrastructure. Conclusion Telepractice holds considerable potential to address healthcare access challenges in Africa, especially for hearing and balance disorders. However, systemic barriers related to infrastructure, resources, and training need to be addressed to ensure long-term success. Future policies should focus on enhancing technological infrastructure, providing affordable internet access, and integrating telepractice into healthcare training programmes. Further research is necessary to explore context-specific solutions and optimize the delivery of telepractice services in Africa.